Hypohidrosis or hyperhidrosis? Ross syndrome - Didem Mullaaziz; Aslı Feride Kaptanoglu; Amber Eker (Wolters Kluwer Medknow Publications, 2016)
Ross syndrome is a rare clinical disorder of sweating associated with areflexia and tonic pupil. The most disturbing symptoms are segmental compensatory hyperhidrosis and heat intolerance. There are few reports of Ross syndrome in the dermatological literature. In this report, we present a case of a 40-year-old man with a 5-year history of hemifacial hyperhidrosis as his primary complaint. This report intends to inform physicians, especially dermatologists and neurologists, of the presence of this complex disorder.